Acute electronic vapour product whole aerosol exposure of 3D human bronchial tissue results in minimal cellular and transcriptomic responses when compared to cigarette smoke. (26th February 2021) - Phillips, Gary; Czekala, Lukasz; Behrsing, Holger P; Amin, Khalid; Budde, Jessica; Stevenson, Matthew; Wieczorek, Roman; Walele, Tanvir; Simms, Liam
The use of electronic vapour products (EVPs) continues to increase worldwide and with advances in cell culture systems, molecular biology and the computational sciences there is also accumulating evidence of their potential reduced toxicity and reduced potential harm when compared to cigarette smoke. To further understand the potential risks and health effects associated with exposure to EVP aerosols we have assessed the cellular and transcriptomic response from a commercially available lung tissue culture system (MucilAir TM ) following a single sub-cytotoxic exposure to cigarette smoke and the equivalent nicotine delivered dose of EVP aerosol. The transcriptomic, cellular (cilia beat frequency (CBF) and percent active area (%AA), trans epithelial electrical resistance (TEER), histology) and cytokine release were assessed at 4- and 48- hours following recovery from air, EVP aerosol (8.4% V/V: myblu TM blueberry flavour, 2.4% nicotine) and 3R4F smoke (3.5% V/V: exposure). No pathological changes were observed at either recovery time point from any exposure. Air and EVP aerosol exposure had no effect on CBF, %AA nor TEER at 48 hours. Exposure to cigarette smoke resulted in a decrease in TEER, an increase in CBF and the release of proinflammatory cytokines at both recovery time points. Although the number of significantly expressed genes was minimal following exposure to EVP aerosol, exposure to 3R4F smoke resulted in a significant upregulation of several disease relevant pathways. These data provide evidence that following an acute exposure to EVP aerosol there is significantly less damage to lung cells in culture than the equivalent, nicotine based, dose of cigarette smoke.